An update on Scaponopselaphus Scheerpeltz (Coleoptera: Staphylinidae) with the description of three new species, and a key to the species - Louri Klemann-Junior; Angélico Asenjo; Bruno Gouvea; Roberta M. Valente (PLoS ONE, 2025)
Three new species of the genus Scaponopselaphus Scheerpeltz, 1972 are described; Scaponopselaphus caribi sp. nov., and Scaponopselaphus oby sp. nov. from Brazil, and Scaponopselaphus paradoxus sp. nov. from Peru. New locality for Scaponopselaphus mutator (Sharp, 1876) is recorded. Major diagnostic features and pictorial and dichotomic identification key are provided for all species of the genus.